Evaluation of Ecosystem Services related to Bio-Energy Landscape Connectivity (BELC) for land use decision making across different planning scales. (February 2016) - Pelorosso, R.; Gobattoni, F.; Geri, F.; Monaco, R.; Leone, A.
Highlights: A new index of Bio-Energy Landscape Connectivity (BELC). Ecosystem Services relating to BELC are evaluated by PANDORA model. Influence of different planning scales on Ecosystem Services and BELC evaluation. PANDORA model ensures applicability at different scales and in data scarcity contexts. Abstract: Landscape connectivity is of paramount importance not only in maintaining both functionality and resilience of social-ecological systems, but also in providing Ecosystem Services (ESs). Despite recent efforts, several issues still need to be faced to fully integrate ESs evaluation relating to landscape connectivity into effective plans and environmental assessment procedures. Choosing an appropriate scale of analysis is one of the most problematic topics, since it can profoundly affect the evaluation of single patch contribution to global connectivity. Moreover, the effect of different scales on ESs assessment based on spatial modelling has not yet been investigated. In this paper, an innovative approach to the assessment of Bio-Energy Landscape Connectivity (BELC) and related ESs for Biodiversity conservation, is presented, based on the PANDORA 3.0 landscape evolution model. A new index (dMtot) for the evaluation of each patch's contribution to global BELC is proposed and employed to build a new formulation for the assessment of ESs in monetary terms. A set of Non Urbanized Areas (NUAs) is therefore analyzed in the Metropolitan area of Bari (Southern Italy) across three planning scales commonly adopted in planning practice. The results bring to light the sensitivity of evaluation to the choice of scale, underlining the need to consider a higher level of analysis when local plans are drawn up for land use decision making. A thorough evaluation of this larger extension could therefore require more resources. As a result, modelling approaches that are less data and time consuming would become even more necessary. In this view, the PANDORA 3.0 model could provide a valid and reliable support, since it uses data that are usually available to land managers (e.g. land cover/land use maps, soil maps, Digital Elevation Models). Moreover, it could also be employed to assess land use scenarios at different scales relatively quickly. Limits of the current approaches and research challenges are then discussed. The final goal of the article is to provide an additional tool, which will allow ESs and Landscape Ecology concepts to be integrated not only into assessment procedures (e.g. EIA, SEA) but also into landscape and urban planning practice.